Fecal Microbiota Transplantation Research over the Past Decade: Current Status and Trends - Shaodong Hao; Shanshan Yang; Naiwei Zhang; Hongjie Cheng (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Fecal microbiota transplantation (FMT) is a current research hotspot, with a surge in the output of publications over the past decade. This study dedicates to the exploration of the research status and highlights significant themes and future trends in FMT research with the aid of bibliometric analysis. Methods. FMT publications from 2012 to 2021 were retrieved on August 12, 2022, using the SCI-Expanded of Web of Science (WoS). The Bibliometrix in R program, Microsoft Office Excel, VOSviewer, and CiteSpace were utilized for bibliometrics and visual analysis, revealing the main publications, journals, countries, agencies, authors, and keywords distribution in FMT research. Results. There were 2,931 papers included. FMT research presented a growing trend from 2012 to 2021. The countries with the most publications and contributions in FMT area were China and the United States. The high-yield institutions were Harvard University, Udice French Research Universities, and the University of California System. The primary authors were Nieuwdorp Max, Allegretti Jessica R, and Kassam Zain. Frontiers in Microbiology and Science were the top-ranked journals in publications and total citations, respectively. The important topics primarily included FMT-related mechanisms and the usage of FMT in Clostridium difficile infection (CDI), inflammatory bowel disease (IBD), irritable bowel syndrome (IBS), metabolic disease, neurological disorders, and psychiatric disorders. Future research would primarily concentrate on neurological disorders, chemotherapy and immunotherapy for malignant tumors, and FMT-related consensus and guidelines. Conclusion. With the help of bibliometric analysis, we were able to obtain the understanding of the status and trends of global FMT-related research. The field of FMT is undergoing tremendous progress, and our findings can guide clinical researchers’ and practitioners’ future work in the rapidly evolving field of FMT.